Human resources management practices and turnover intention among manufacturing employees in Selangor - Nor'atikah, Baharil (2018)
Employee‟s turnover intention has become one of the most common issues to be discussed nowadays in human resource practices field. However it is vital issue to be further discussed and explore as Malaysia in year 2015 was the third country in South East Asia with the highest voluntary turnover rate approximately 9.5%. This has caused fear among human resources practitioner for looking a way out. The main objective of this study is to examine the relationship between turnover intention and job security, compensation, performance appraisal and career development opportunities among manufacturing industry local employees within Selangor. Data collections for this study were made through a set of questionnaire given to 5 different companies around Selangor which comprised of 265 local employees respondents. Statistical Package for the Social Sciences (SPSS) version 18 software was used in this study in determining the acceptance of the identified hypotheses made specifically for the study. The findings resulted in the acceptance two of the study hypotheses made. Job security and compensation were found to be correlated and contributing to the intention of leaving an organization for manufacturing industry local employees around Selangor. On the other hand, performance appraisal and career development opportunity were found no significant relationship in this study. With limited resource and literature in the study findings, to some extent have contributed in the understanding of the intention to leave an organization among manufacturing industry local employees and developing and expanding the knowledge within the scope of human resource practices in Malaysia employment landscape.